Unlocking the Growth Potential of Poplar: A Novel Transcriptomic-Metabolomic Approach to Evaluating the Impact of Divergent Pruning Strategies - Xiaoting Liu; Kewei Cai; Qinhui Zhang; Weizi An; Guanzheng Qu; Luping Jiang; Fusen Wang; Xiyang Zhao (Plants)
Pruning is a common forest-tending method; its purpose is to promote growth and improve the overall stand quality. Poplar is a fast-growing, broad-leaved tree species with high ecological and economic value. It is a common management method to promote its growth by pruning and adjusting the spatial structure of the stand, but its potential regulatory mechanism remains unclear. In this study, transcriptome and metabolome data of different parts at all pruning intensities were determined and analyzed. The results showed that 7316 differentially expressed genes were identified in this study. In the plant hormone signal transduction pathway, candidate genes were found in eight kinds of plant hormones, among which the main expression was gibberellin, auxin, and brassinosteroid. Some candidate gene structures (beta-glucosidase, endoglucanase, hexokinase, glucan endo-1, 3-beta-D-glucosidase, beta-fructofuranosidase, fructokinase, maltase-glucoamylase, phosphoglucomutase, and sucrose) were specifically associated with starch and sucrose biosynthesis. In the starch and sucrose biosynthesis pathway, D-fructose 6-phosphate, D-glucose 1,6-bisphosphate, and glucose-1-phosphate were the highest in stems and higher in the first round of pruning than in no pruning. The bHLH plays a key role in the starch and sucrose synthetic pathway, and AP2/ERF-ERF is important in the plant hormone signal transduction pathway. These results laid a foundation for understanding the molecular mechanism of starch and sucrose biosynthesis and provided a theoretical basis for promoting tree growth through pruning.